PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V SD NEGERI MANGUNHARJO - Nabila Aulanisya; Leo Charli; Sujarwo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the significant learning outcomes of Pancasila Education fifth-grade students at SD Negeri Mangunharjo after implementing the Snowball Throwing learning model. The research method used is a quasi-experimental design. The population in this study was all 16 fifth-grade students at SD Negeri Mangunharjo, and the sample was 16 fifth-grade students, consisting of 10 boys and 6 girls, selected using saturated sampling technique. The data collection techniques used a multiple-choice test with 14 questions. The data analysis techniques used the z-test. Based on the data analysis, the average pre-test score was 48,21 and the average post-test score was 82,14. The confidence level of α = 0,05 the results showed zcount of ,34 and the ztable of 1,64. Since the calculated zcount > ztable, Ha is accepted and Ho is rejected. From the results of the data analysis, concluded that the Pancasila Education learning outcomes for grade V students at SD Negeri Mangunharjo after applying the Snowball Throwing learning model significantly the KKTP (Learning Objective Achievement Criteria).